Perancangan Sistem Disaster Recovery Pada Instansi Perbankan : Studi Kasus Bank Swasta - Elis Sondang Dasawati (Institut Bisnis dan Informatika Kwik Kian Gie, 2020)
PT. Bank XYZ is a private bank that has and uses many applications in carrying out operationalactivities. However, companies also experience problems that can cause damage to companyassets. To overcome this, banking companies develop a system recovery procedure that must becarried out in the event of damage to these assets. In conducting research and system design, theauthor uses guidelines such as the basic steps that must be carried out in making BC (BusinessContinuity) / DR (Disaster Recovery) and checklists recovery steps for emergency response andrecovery that can be changed according to the individual needs of the organization and system.This research will be conducted using the waterfall software development method, which is asystem development method that has a sequential nature so that this type of development model isvery neat to be grouped, managed, and monitored at each stage. The results of the design that havebeen made are in the form of a web application that has responsive features so that the system canbe accessed anywhere and anytime.Keywords: Disaster Recovery System, Checklists Recovery, Waterfall Model.